ANALYSIS OF FACTORS AFFECTING INCOME INEQUALITY IN BENGKULU PROVINCE IN 2017-2021 - Hana Silvia; Muhammad Arif (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
One of the challenges to economic progress in any country is inequality. Inequality in welfare shows that there are still many upper and lower classes in society and differences in income distribution are thought to widen the gap between rich and poor people. This study aims to identify factors contributing to income inequality in Bengkulu Province. This research is quantitative. The method used is OLS regression analysis with an economic model (estimator). In this study, income inequality is a dependent variable. At the same time, the number of poor population, GRDP, HDI, and LOR are independent variables to determine which characteristics influence income inequality most. The LOR and HDI variables are study factors that provide results with a strong negative influence. Meanwhile, the GRDP and the proportion of the poor have a beneficial and considerable impact.